The Development of Immunotherapy Strategies for the Treatment of Type 1 Diabetes - Coppieters, Ken; von Herrath, Matthias (Frontiers in Medicine, 2018)
Type 1 diabetes is characterized by the progressive loss of pancreatic beta cell function, eventually culminating in patients’ dependence upon exogenous insulin to control blood glucose. Despite continuing improvements in insulin therapy, the majority of patients fail to adequately control their glucose homeostasis, resulting in both short-term (hypoglycemia) and long term (nephropathy, retinopathy, neuropathy and others) complications. This well-documented fact points toward a significant unmet medical need and constitutes the incentive to develop disease modifying therapies in addition to symptomatic treatments. Disease modifying therapies by definition are designed to tackle the underlying cause of the condition. We know since decades that T1D is associated with autoantibodies and inflammatory infiltration of the pancreatic islets. Early genetic evidence revealed a profound contribution of the HLA region, in particular class II. With the advent of the GWAS era, many of the susceptibility regions were shown to code for proteins important in immune function and considerable overlap was found with the genetic signature of other autoimmune conditions. The combined evidence thus overwhelmingly favors a pivotal role of leukocytes, and especially T cells, during beta cell destruction. The T cell repertoire associated with T1D development is by all accounts diverse and is directed against beta cell specific molecules such as insulin, as well as autoantigens that are also expressed in other tissues, such as GAD. Although some progress has been made in using T cell signatures as disease biomarkers in individual patients, the kinetics and composition of these repertoires still appear to be largely unpredictable. One of the reasons may be that these parameters are typically measured in blood samples without the possibility of linking any observations to events at the target organ, which is extremely difficult to biopsy.